Dye powder ability of broken bone tree bark on silk fibers with direct and mordant dye method - Chatjutamanee , Warunthip (Food Agricultural Sciences and Technology, 2019)
This research aims to produce the natural dye powder from broken bone tree bark and study the adsorption of dye on silk fibers. Dye from broken bone tree bark was prepared by putting the part of these plants in boiling water for 60 minutes and filter the solution extract. The solvent was evaporated and solid dye was collected. The result yielded a light brown powder. An adsorption of dyes on silk fibers was studied by UV-Visible spectrophotometer. The absorption spectra of broken bone tree bark showed lmax at 296 nm. The direct dye method suitable for broken bone tree bark was found that the conditions for silk fiber dyeing were dye concentration at 75 mg / L, 80 °C, 10 minutes, pH 6. The dye ability of broken bone tree bark of silk fibers showed the highest value about 3.93 mg /g silk. The mordant dye method suitable for broken bone tree bark demonstrated that the conditions for silk fiber dyeing were as follows dye concentration was 75 mg / L,80 °C,10 minutes by mordant from spinach ashes pH 9.9.The dye ability of broken bone tree bark on silk fibers showed the highest value about 8.54 mg / g silk.